Communicating change: Reform and resistance in embracing change in curriculum - Yusof, Norhafezah; Awang Hashim, Rosna; Badusah, Jamaludin; Konting, Majid; Chan, Kok Kian (2011)
In line with proposals in the current literature, the researchers conducted a qualitative based study to investigate reactions of respondents toward the introduction of change in Higher Learning Institutions in Malaysia. The change in question is the introduction of a new model of curriculum. The methods employed were structured interviews based on ArmenakisS Five Sentiments of Change. Findings revealed that all the five sentiments were positively associated with participants from newly established universities. In contrast, for participants from established universities, there was more resistance. Misalignment of top management approaches with aspirations espoused by the Ministry, and the anticipation of a heavy workload by facilitators are amongst the major factors why change was resisted.